ISOLATION, SEQUENCING AND IN SILICO CHARACTERIZATION OF PROMOTER REGION OF HSPA6 GENE FROM ARABIAN CAMEL (CAMELUS DROMEDARIES) - M. Elrobh; M. Alanazi; Z. Abduljaleel; W. El-Huneidi; W. Khan (Journal of Animal and Plant Sciences, 2017)
Heat-shock proteins, divided in numerous families, play an important role in cellular processes. The human Hsp70 (PDB ID 1HJO) performs multiple steps including protein folding, trafficking, remodeling and degradation. In addition, the Hsp70 is also involved in cell signaling, and tumor repression. We have previously sequenced the full-length cDNA encoding the putative stress induced heat shock protein HSPA6 from Arabian camel (NCBI Gene Bank accession number HQ214118.1). The sequence analysis of HSPA6 gene revealed a 1932bp-long open reading frame encoding 643 amino acids. In this work, we extended our study to explore the mechanism that manages the HSPA6 gene expression by isolating and characterizing the flanking 5’ region using online tools, expected to harbor the regulatory elements. The straight-walk method was used to isolate the upstream genomic DNA sequences of the HSPA6. The isolated fragment has a length of 1417bp and after verifying the sequence, it was deposited in GenBank under accession number JX888464. The sequence analysis revealed the presence of several heat shock elements (HSEs) that act as binding sites for the major heat shock factor. These HSE sites were dispersed in the isolated region and had consensus sequences identical to those found in eukaryotes. Other core promoter elements such as potential transcriptional start site for the HSPA6 gene were found including the canonical TATA-box, DPE, MTE, BRE, CpG island, palindromic and repeated sequences. Taken together, this is the first report on the promoter region of the HSPA6 gene from Arabian camel which will enhance our understanding of how such regulatory cis-elements are engaged in regulating the gene expression.
Keywords: genome walk; heat shock elements; HSPA6 gene; Camelus dromedaries; in silico